2006
DOI: 10.1158/0008-5472.can-06-1484
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and Overexpression ofCTTN(EMS1) Contribute to the Metastasis of Esophageal Squamous Cell Carcinoma by Promoting Cell Migration and Anoikis Resistance

Abstract: Gain of chromosome 11q13 is a common event in esophageal squamous cell carcinoma (ESCC). The cortactin gene (CTTN, also EMS1), located at 11q13, plays a pivotal role in coupling membrane dynamics to cortical actin assembly. This gene has been implicated in the motility of several types of cells. In the present study, we found that the amplification and overexpression of the CTTN gene was associated with lymph node metastasis in ESCC. Functional analysis by small interfering RNA-mediated silencing of CTTN revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
161
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 37 publications
8
161
0
1
Order By: Relevance
“…Downregulation of cortactin in cancer cell lines decreases the cellular motility and ability to migrate (Rothschild et al, 2006;van Rossum et al, 2006) whereas overexpression resulted in an increased invasive potential (van Rossum et al, 2003;Rothschild et al, 2006). In addition to the effect on cell migration by mediating actin polymerization and cell adhesion (van Rossum et al, 2006), cortactin might also influence cell migration and metastasis by anoikis resistance and PI3K/Akt signalling (Luo et al, 2006;Luo and Wang, 2007). Because of these biological functions and its overexpression due to DNA amplification, cortactin is the most likely gene within the 11q13.3 amplicon to mediate the worse clinical behaviour of late stage LSCC with 11q13 amplification.…”
Section: Discussion Cortactin Predicts Poor Survival In Late Stage Lamentioning
confidence: 99%
See 3 more Smart Citations
“…Downregulation of cortactin in cancer cell lines decreases the cellular motility and ability to migrate (Rothschild et al, 2006;van Rossum et al, 2006) whereas overexpression resulted in an increased invasive potential (van Rossum et al, 2003;Rothschild et al, 2006). In addition to the effect on cell migration by mediating actin polymerization and cell adhesion (van Rossum et al, 2006), cortactin might also influence cell migration and metastasis by anoikis resistance and PI3K/Akt signalling (Luo et al, 2006;Luo and Wang, 2007). Because of these biological functions and its overexpression due to DNA amplification, cortactin is the most likely gene within the 11q13.3 amplicon to mediate the worse clinical behaviour of late stage LSCC with 11q13 amplification.…”
Section: Discussion Cortactin Predicts Poor Survival In Late Stage Lamentioning
confidence: 99%
“…Gene by gene functional analyses have revealed that cyclin D1 (Opitz et al, 2001;Nelsen et al, 2005), FADD (Alappat et al, 2003;Chen et al, 2005) and cortactin (van Rossum et al, 2003;Luo et al, 2006) are potentially able to enhance cancer development. However, these studies do not account for the effect of multiple genes located within the 11q13.3 amplicon.…”
Section: Discussion Cortactin Predicts Poor Survival In Late Stage Lamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the functional properties of cortactin, together with amplification of chromosome locus 11q13, suggest a link between its overexpression and tumour invasion and/or metastasis. Accordingly, in several animal models ectopic overexpression of cortactin has been shown to accelerate tumour dissemination, and decreased expression of cortactin, by RNA interference, leads to impaired tumour cell migration and metastasis (Li et al, 2001;Chuma et al, 2004;Hill et al, 2006;Luo et al, 2006).…”
mentioning
confidence: 99%